2012
DOI: 10.1371/journal.ppat.1002911
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclase-Associated Protein Cap1 Is Important for Proper Regulation of Infection-Related Morphogenesis in Magnaporthe oryzae

Abstract: Surface recognition and penetration are critical steps in the infection cycle of many plant pathogenic fungi. In Magnaporthe oryzae, cAMP signaling is involved in surface recognition and pathogenesis. Deletion of the MAC1 adenylate cyclase gene affected appressorium formation and plant infection. In this study, we used the affinity purification approach to identify proteins that are associated with Mac1 in vivo. One of the Mac1-interacting proteins is the adenylate cyclase-associated protein named Cap1. CAP ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 92 publications
(124 citation statements)
references
References 73 publications
(116 reference statements)
4
118
1
1
Order By: Relevance
“…It was recently demonstrated that an Adenylate cyclase associated protein, Cap1, localized as bright spots in the cytoplasm of the infection hyphae in M. oryzae [77]. However, we could not detect such punctate localization pattern for Rgs1-mC during infectious growth.…”
Section: Discussioncontrasting
confidence: 90%
“…It was recently demonstrated that an Adenylate cyclase associated protein, Cap1, localized as bright spots in the cytoplasm of the infection hyphae in M. oryzae [77]. However, we could not detect such punctate localization pattern for Rgs1-mC during infectious growth.…”
Section: Discussioncontrasting
confidence: 90%
“…Molecular characterization of the MAC1 adenylate cyclase and CPKA catalytic subunit of PKA genes ( Figure 1) further confirmed the role of cAMP signaling in surface recognition [1]. Recently, the CAP1 gene was shown to be involved in association with the actin cytoskeleton and Mac1 activation [4]. Several components of heterotrimeric G-proteins, including Ga MagA or MagB, Gb Mgb1, and Gg Mgg1, that function upstream from the cAMP-PKA pathway also have been characterized [5].…”
Section: Camp Signaling Regulates Surface Recognition and Pathogenesismentioning
confidence: 66%
“…However, mutants defective in cAMP signaling, such as the mgb1, mac1, and cap1 mutants, are known to produce spontaneous suppressors (Fang and Dean 2000;Nishimura et al 2003;Zhou et al 2012). The efficiency of appressorium formation on hydrophilic surfaces and the formation of melanized hyphal tips were often reduced in subcultures.…”
Section: Discussionmentioning
confidence: 99%